The safety and efficacy of otilimab for rheumatoid arthritis: a systematic review and meta-analysis of randomized controlled trials - Abdelrahman Mahmoud; Salem Elshenawy; Ahmed A. Ibrahim; Yasmine Adel; Yehya Khlidj; Ali M. Al-Khalaileh; Majd M. AlBarakat; Salma Allam; Mohamed Abuelazm (The Egyptian Journal of Internal Medicine)
Abstract Background Rheumatoid arthritis (RA) is a chronic autoimmune disease characterized by joint inflammation and damage, affecting millions globally. Despite treatment advancements, achieving remission remains a challenge. Granulocyte–macrophage colony-stimulating factor (GM-CSF), elevated in RA, is a promising therapeutic target. Otilimab, a GM-CSF-blocking antibody, showed promising potential in clinical trials. Methods We systematically searched PubMed, Web of Science, and Scopus databases until Mar 2, 2024. For dichotomous outcomes, we employed the risk ratio (RR). We used the mean difference (MD) with a 95% confidence interval (CI) for continuous outcomes, utilizing the random-effects model to pool the results (PROSPERO ID: CRD42024527342). Results Three publications reporting four trials were included, with 3933 patients. Moderate-certainty evidence demonstrated that otilimab significantly increased ACR responders compared to placebo, both in the 90 mg group (RR, 1.50; 95% CI 1.14, 1.98; P < 0.0001) and the 150 mg group (RR, 1.39; 95% CI 1.12; 1.73, P < 0.0001). High-certainty evidence suggests that otilimab, at both 90 mg and 150 mg doses, did not differ significantly from placebo in terms of experiencing any adverse events (90 mg: RR, 1.02; 95% CI [0.92, 1.13]; P = 0.71; 150 mg: RR, 1.03; 95% CI [0.89, 1.19]; P = 0.73). Conclusion Otilimab shows a favorable balance of efficacy and safety over placebo in RA treatment, but it is less effective than tofacitinib. These findings support GM-CSF inhibition as a viable therapeutic strategy and provide a basis for further development of more effective RA-targeted therapies.